국가표준식품성분 데이터베이스 대표시료 선정을 위한 표본설계 - 김진흠; Jinheum Kima; 황해원; Hae-won Hwanga; 조유정; Yu Jung Choa; 박진우; Jinwoo Parka (Ŭngyong tʻonggye yŏnʼgu, 2020)
농촌진흥청에서는 식품산업진흥법 제19조 제1항에 의거하여 국가표준식품성분표를 5년 주기로 발표하고 있다. 본 논문에서는 2021년 국가표준식품성분표 제10개정판 발간을 앞두고 우리나라 국민들이 많이 소비하고 있는 식품으로 선정된 182개 식품의 대표시료를 합리적이고 과학적으로 추출하기 위한 방안을 제안하였다. 농수산물을 포함한 식품을 판매하는 식료품점을 유통형태에 따라 대형마트와 전통시장으로 구분한 후 NFNAP에서 제안한 층화다단추출법을 각각 적용하여 8개 표본을 추출하였다. NFNAP는 미국인들이 소비하고 있는 식료품의 성분표에 대한 신뢰성 있는 추정을 담보하기 위해 미국 농무성과 국립보건원이 1977년에 협약을 맺고 공동 연구로 개발한 국가식품 영양분석 프로그램이다. 대형마트에 기초한 표본추출에서는 이마트 가양점, 홈플러스 시흥점, 롯데마트 동두천점, 이마트수원점, 롯데마트 둔산점, 롯데마트 여수점, 이마트 울산점, 하나로클럽 울산점이 표본으로 추출되었고, 전통시장에 기초한 표본추출에서는 서울시 금천구 독산동우시장과 송파구 풍납시장, 고양시 일산서구 일산시장, 광주광역시 북구 운암시장, 대전광역시 대덕구 법동시장, 부산광역시 영도구 봉래시장과 해운대구 좌동재래시장, 창원시 진해구 중앙시장이 표본으로 추출되었다. Under Article 19, Paragraph 1 of the Food Industry Promotion Act, Rural Development Administration renews the Korean foods composition table every five years. Before the publication of the tenth revision of the Korean foods composition table in 2021, this paper suggests methods for collecting representative samples of 182 highly consumed foods in Korea. Food markets are categorized by their distribution channels, which are supermarkets and local markets. Eight samples are collected from each category by applying the National Food and Nutrient Analysis Program (NFNAP)’s stratified multi-stage sampling. The NFNAP was implemented in 1997 as a collaborative food composition research effort between the National Institute of Health (NIH) and the US Department of Agriculture (USDA) to secure reliable estimates for the nutrient content of food and beverages consumed by the US population. Selected supermarkets for selecting representative food samples are Emart Kayang, Homeplus Siheung, Lottemart Dongducheon, Emart Suwon, Lottemart Dunsan, Lottemart Yeosu, Emart Ulsan, and Hanaroclub Ulsan. Selected local markets also are Doksandongusijang in Geumcheon-gu and Pungnapsijang in Songpa-gu, Seoul, Ilsansijang in Ilsanseo-gu, Goyang, Unamsijang in Buk-gu, Gwangju, Beopdongsijang in Daedeok-gu, Daejeon, Bongnaesijang in Yeongdo-gu and Jwadongjaeraesijang in Haeundae-gu, Busan, and Jungangsijang in Jinhae-gu, Changwon.